Ocular manifestations of Fabry's disease: data from the Fabry Outcome Survey. Issue 2 (14th September 2006) - Sodi, Andrea; Ioannidis, Alexander S; Mehta, Atul; Davey, Clare; Beck, Michael; Pitz, Suzanne
Abstract : Background: Fabry's disease is an X-linked lysosomal storage disorder characterised by deficient activity of the enzyme α-galactosidase A. Aim: To study eye abnormalities in patients with Fabry's disease in the Fabry Outcome Survey (FOS). Methods: This is the largest study of ocular manifestations in patients with Fabry's disease. In all, 173 of the 688 patients enrolled in FOS underwent a detailed ophthalmic examination, with a special focus on abnormalities of the cornea, lens, conjunctival and retinal vessels. Results: Cornea verticillata was reported in 76.9% of females and 73.1% of males; vessel tortuosity was observed in 21.9% of females and in 48.7% of males. Fabry cataract was recorded in 9.8% of females and in 23.1% of males. Cornea verticillata was therefore the most frequently reported ophthalmic abnormality in Fabry's disease in both hemizygotic males and heterozygotic females. Tortuous conjunctival and retinal vessels and Fabry cataract were more frequently found in males than in females. Vessel tortuosity was more frequently observed in patients with a higher severity score and greater impairment of renal and cardiac function, suggesting that it may be associated with a more severe disease. The youngest patient with ocular changes was 3 years old. The prevalence of tortuous vessels in males increased with age. Conclusion: The presence of cornea verticillata is a useful aid in the diagnosis of Fabry's disease, as it is often present at the time of diagnosis. Vessel tortuosity may have some predictive value for systemic involvement.